Beneficiary reactions to the fodder bank trials - Taylor-Powell, E.; Ingawa, S.A. (International Livestock Centre for Africa, 1986)
Examines ILCA's fodder bank programme w. regard to costs, benefits and beneficiaries, perception of them, relating this to acceptability of this innovation by Fulani pastoralists.